Productivity growth and the role of mechanisation in African agriculture - Kirui, Oliver K.; Kornher, Lukas; Beckchanov, Maksud (Informa UK Limited, 2023)
This paper compares agricultural productivity growth, specifically, the impact of agricultural mechanisation on total factor productivity and cereal yields, across African countries using contemporaneous and sequential Malmquist index approaches. Contemporaneous approach findings indicate that agricultural productivity grew by 1% annually over 1961–2014, while sequential technology measures show much higher growth of 1.7%. The highest growth rates were experienced since the 2000s due to technical progress. Regression analysis indicates that mechanisation, research and development, weather conditions, and population pressure influence African agricultural productivity. Climate-smart options to sustain crop yields in countries relying heavily on rain-fed agriculture are critical. The transfer of knowledge from countries with high-level productivity might enhance productivity in “laggard” countries.